2004
DOI: 10.1111/j.1538-7836.2004.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

The no‐reflow phenomenon in coronary arteries

Abstract: Summary.  No reflow occurs when there is inadequate myocardial perfusion of a given segment of the coronary circulation without evidence of epicardial vessel obstruction. It is a rare but clinically significant condition associated with myocardial infarction and coronary interventions. Diagnosis is usually based on clinical signs of myocardial ischemia (symptoms and/or ECG changes) combined with coronary angiography. Management can be difficult and primarily consists of intracoronary administration of vasodila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
1
10
0
2
Order By: Relevance
“…For statistical analysis, the cohort was divided in two subsets according to the MRI score of microvascular obstruction: low score (0-1) and high score (2)(3). Data are expressed as mean ± SD.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…For statistical analysis, the cohort was divided in two subsets according to the MRI score of microvascular obstruction: low score (0-1) and high score (2)(3). Data are expressed as mean ± SD.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…It is widely recognized that, although mechanical or pharmacological reperfusion is essential for the survival of ischemic tissues, reperfusion can promote a variety of adverse events in cardiac myocytes and coronary microvasculature [1,2]. Previous studies using contrast echography, technetium scintigraphy, blush angiographic score, and magnetic resonance imaging (MRI) demonstrated that despite recanalization of the infarct-related artery, up to 30% of patients undergoing PCI lack efficient myocardial International Journal of Cardiology 121 (2007) 139 -147 www.elsevier.com/locate/ijcard reperfusion [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, primary percutaneous coronary intervention (PCI) is the reperfusion strategy of choice in patients with STEMI [1]. However, while reopening of the epicardial vessel is usually successful, there is inadequate myocardial reperfusion in 10-40 % of patients [2][3][4][5][6]. This so-called no-reflow (or slow-reflow) phenomenon is defined by post-procedural ''thrombolysis in myocardial infarction'' (TIMI) flow \3 or myocardial blush grade 0 or 1 in the case of a TIMI 3 flow or STsegment resolution \70 % within 4 h of revascularization [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that platelet and thrombus embolization, associated with primary coronary intervention, constitute a major cause of no-reflow in humans, and this can impact noreflow independently of the size of the area at risk [2,24]. In this setting, prompt recognition of unsuccessful tissue reperfusion becomes of paramount importance.…”
Section: Discussionmentioning
confidence: 96%